Legal Review of Criminal Acts of Motor Vehicle Theft Accompanied by Violence - Marseli R.A Lama Tokan (Journal of Law Justice (JLJ), 2025)
This study aims to analyze the factors causing theft accompanied by abuse and to assess the effectiveness of countermeasures taken by the Sorong City Police. The research method used is a combination of normative and empirical legal research, utilizing primary data obtained through interviews at the Sorong City Police Station and secondary data in the form of laws, regulations, literature, and related documents. The novelty of this research lies in the integration of juridical analysis and empirical findings related to the characteristics of theft cases accompanied by violence in the Sorong area, as well as how the pattern of cooperation between the police and the community can form a community-based prevention mechanism. The results of the study show that the increase in cases of theft with abuse is generally triggered by economic factors, lack of environmental supervision, and open opportunities for crime. Cases are handled through the collection of evidence, examination of witnesses who clearly saw the incident, and tracing the chronology to fulfill the elements of a criminal offense as stipulated in Articles 362–367 of the Criminal Code and Articles 351–355 of the Criminal Code. On the other hand, prevention efforts have not been fully optimal due to limited police resources and minimal community involvement. In conclusion, theft accompanied by abuse can be reduced through increased socialization of crime prevention, strengthening of neighborhood security systems such as neighborhood watch posts, and strategic collaboration between the Sorong City Police and the community to build collective awareness and reduce opportunities for crime.